PENGARUH PROFITABILITAS, LEVERAGE DAN UKURAN PERUSAHAAN TERHADAP PENGHINDARAN PAJAK (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2020–2024) - Algian Khalish Wardhana; Wahyu Meiranto (Diponegoro Journal of Accounting, 2025)
This study aims to examine the effect of profitability, leverage, and firm size on tax avoidance. The research was conducted on manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The sample was selected using a purposive sampling method based on specific criteria, resulting in 1,105 firm-year observations. The analytical method used in this study is Partial Least Squares Structural Equation Modeling (PLS-SEM).The findings reveal that profitability has a significant positive effect on tax avoidance, suggesting that more profitable companies tend to engage in tax minimization strategies. Meanwhile, leverage and firm size do not have a significant effect on tax avoidance, indicating that these variables do not substantially influence corporate tax avoidance behavior in the Indonesian manufacturing sector.